Dinuclear copper(i) complexes with N-heterocyclic thione and selone ligands: synthesis, characterization, and electrochemical studies1. Issue 37 (7th October 2015) - Kimani, Martin M.; Watts, David; Graham, Leigh A.; Rabinovich, Daniel; Yap, Glenn P. A.; Brumaghim, Julia L.
<x xml:space="preserve">Abstract</x> We report dinuclear copper(i) complexes with a variety of monodentate and bidentate thione- and selone-containing ligands. Cu(ii/i) potentials were tuned in a 470 mV range depending on the chalcogenone ligands.